A rigid organic ligand-induced POMCP with a helical self-penetrating structure as a redox and acid catalyst. Issue 37 (23rd August 2016) - Sha, Jing-Quan; Zhu, Pei-Pei; Yang, Xi-Ya; Sheng, Ning; Li, Ji-Shen; Sun, Long-Jiang; Yan, Hong
Abstract : By the utilization of rigid organic ligands, a new POMCP with inorganic helical configuration features was isolated, which displays good acid-catalytic activity and photocatalytic selectivity. Abstract : By the utilization of rigid organic ligands, a new POMCP with inorganic helical configuration features was isolated and structurally characterized, in which inorganic double chains are constructed from POMs and single Ag ions, and the contribution of the rigid ligand to the helical structure of POMCPs is firstly reported and discussed. In particular, the new POMCP displays good acid-catalytic activity toward the synthesis of aspirin and photocatalytic selectivity for the degradation of organic dyes, as well as excellent photocatalytic activity toward the degradation of MB. Finally, the catalytic reaction kinetics are also discussed.